Percutaneous mitral valve repair with the mitraclip® system. Issue 7 (26th February 2013) - Paranskaya, Liliya; D'Ancona, Giuseppe; Bozdag‐Turan, Ilkay; Akin, Ibrahim; Kische, Stephan; Turan, Gökmen R.; Divchev, Dimitar; Rehders, Tim; Westphal, Bernd; Schubert, Jochen; Nienaber, Christoph A.; Ince, Hüseyin
<x xml:space="preserve">Abstract</x> Objectives: The purpose of this study was to compare outcomes using standard clipping (SC) (one to two clips) or multiple clipping (MC) (more than two clips). Background: MitraClip® implantation using MC has been proposed to treat severe mitral regurgitation (MR) in high‐risk patients. Methods and Results: A tailored strategy was used implanting as many clips as required to eliminate MR. A total of 85 consecutive patients [78 ± 6 years, 48 men (56.5%) ] with MR (grade 3+ or 4+) were included. EuroSCORE was 24 ± 12 (2.5–56.3) and STS‐score 12 ± 7 (1.2–31.2). SC was used in 61 (71.8%) and MC in 24 (28.2%) patients. Patients in MC group had larger mitral valve (MV) annuli (P = 0.025), MV orifice areas (MVOA) (P = 0.01), and MR degree (P = 0.005). Successful clip placement was achieved in 82 patients (96.5%). At discharge, no patient had grade 4+ MR. MR 3+ presented in 4 patients (7.0%) in the SC group and in 1 (4.5%) in the MC group (P = 0.72). There were 3 (3.5%) in‐hospital deaths. Follow up (211 ± 173 days, range 4–652) echocardiography confirmed similar MVOA (P = 0.83) and MV gradients (P = 0.54) in the both groups. At linear regression there was no independent correlation between clips number and postoperative MVOA/gradient. One‐year survival was 71.1% without difference between groups (P = 0.74). Conclusion: Although the hemodynamic and anatomical basis of MR may differ, every procedure should aim at eliminating MR. In some patients this goal can be achieved using MC with minimized risk of MV stenosis if preoperative anatomy/mechanism of MV regurgitation are adequately assessed. © 2012 Wiley Periodicals, Inc.